"We could have been leaders": The rise and fall of offshore wind energy on the political agenda in Ireland. (October 2022) - Roux, Jean-Pierre; Fitch-Roy, Oscar; Devine-Wright, Patrick; Ellis, Geraint
Abstract: Many countries have ambitious plans for increasing the generation of electricity from offshore wind energy in the coming decades. Realising these ambitions requires concerted, often innovative, political action across several policy domains. To understand the unique political challenges facing offshore wind deployment, this article presents a case study of the Republic of Ireland, where decades of sporadic political ambition to support offshore wind energy has not yet translated into commercial deployment. We use the Multiple Streams Framework to guide data collection, 29 elite interviews and extensive documentary analysis, and offer an historical explanation for why political actors did not meet long-standing market ambition. We analyse the battle of ideas between alternative policy approaches that emerge through distinct policy networks and institutions spanning marine planning, grid development, and energy price support. In Ireland, two key drivers restrained political support for offshore wind for over a decade: competition with onshore wind for limited grid connection capacity and resilience, and calibration of policy instruments to attain decadal renewable energy target at least cost. The study shows the value of a deviant case to demonstrate the political complexities of developing and adopting technology-specific policy instruments to support offshore wind energy in the context of long-term climate change targets, grid development, and grid system services plans. Highlights: Political support for offshore wind energy entails a 'battle of ideas' that spans marine planning, grid development and connection, and price support instruments Calibration of policy instruments to attain a decadal energy target at least cost can constrain political support for offshore wind energy Limited grid resilience and capacity can constrain political support for offshore wind energy Policy entrepreneurs can tether new offshore wind energy policies to climate change targets An independent electricity regulator and system operator can constrain the ambition of policy entrepreneurs to support offshore wind energy